Impella support compared to medical treatment for post-cardiac arrest shock after out of hospital cardiac arrest. (May 2018) - Karatolios, Konstantinos; Chatzis, Georgios; Markus, Birgit; Luesebrink, Ulrich; Ahrens, Holger; Dersch, Wolfgang; Betz, Susanne; Ploeger, Birgit; Boesl, Elisabeth; O'Neill, William; Kill, Clemens; Schieffer, Bernhard
Abstract: Aims: To compare survival outcomes of Impella support and medical treatment in patients with post-cardiac arrest cardiogenic shock related to acute myocardial infarction (AMI). Methods: Retrospective single center study of patients resuscitated from out of hospital cardiac arrest (OHCA) due to AMI with post-cardiac arrest cardiogenic shock between September 2014 and September 2016. Patients were either assisted with Impella or received medical treatment only. Survival outcomes were compared using propensity score-matched analysis to account for differences in baseline characteristics between both groups. Results: A total of 90 consecutive patients with post-cardiac arrest shock due to AMI were included; 27 patients in the Impella group and 63 patients in the medical treatment group. Patients with Impella support had a longer duration of low-flow time (29.54 ± 10.21 versus 17.57 ± 8.3 min, p < 0.001), higher lactate levels on admission (4.75 [IQR 3.8–11] versus 3.6 [IQR 2.6–3.9] mmol/L, p = 0.03) and lower baseline systolic LVEF (25% [IQR 25–35] versus 45% [IQR 35–51.25], p < 0.001) as compared to patients without circulatory support. After propensity score matching, patients with Impella support had a significantly higher survival to hospital discharge (65% versus 20%, p = 0.01) and 6-months survival (60% versus 20%, p = 0.02). Conclusion: The results from our study suggest that Impella support is associated with significantly better survival to hospital discharge and at 6 months compared to medical treatment in OHCA patients admitted with post-cardiac arrest cardiogenic shock and AMI.